(untitled) (Journal of Education and Development, 2023)
This research explored at the relationship between curricular development and entrepreneurial abilities, using ICT knowledge as a mediator. In this research, a quantitative analysis style was exploited to make course of study with the various aspects of objectives, contents, teaching tactics, feedback, and assessment. At the OUT Universities regional centers in Tanzania, 66 respondents from graduate students and employers completed two sets of questionnaires, one for the graduate’s survey and the other for employers. The findings demonstrate that all aspects of curriculum development (i) have no bearing on entrepreneurial abilities (ii) Educational Environment have influence in Development of Entrepreneurial Skills and Competencies and (iii) have a favorable impact on ICT knowledge. Additionally, all aspects of curriculum development including objectives, contents, teaching methods, and feedback and assessment were found to be favorably connected in the indirect way for the entire development process. Finally, the discussion, conclusions, and practical implications of this study are presented in detail.